Analysis of Approaches on the Protection of Consumer Rights - Gujjar, Muhammad Waqas; Manzoor, Bakhtawar; Rana, Anwaar; Ahmad, Muhammad (Law and Policy Review, 2023)
In an era, characterized by striking globalization affecting every field of life, the very foundations of consumer rights and mechanisms designed to uphold them have undergone a significant evolution on a global scale as well. With the increased inclination towards online shopping, the attitude of consumer and the vendor both have evolved. This evolved attitude tends to call for more diverse regulations at international and domestic level. The current study is an exposition on the consumer rights with the pretext of emerging legal, economic, and social scenarios with the focus on the impact of globalization worldwide. After liberalization of trade, private entities now sell their products directly to the consumers by sitting in one country across the world. The role of big companies has increased in a globalized world especially over the past recent years. Cross-border consumer contracts have become frequent between traders and consumers. Keeping in view the rapid spread of globalization and its effects on consumer rights, there is a significant need for a harmonious and effective mechanism of international rules and regulations for their protection.